Improving Students' Writing Skills by Using Audio-Visual Media - Fadhila Humaira; Rosnani Sahardin; Diana Fauzia Sari (Universitas Syiah Kuala, 2022)
This study aims to determine the result of using audio-visual media on writing skills in the experimental class and control class. In this study, the researcher focuses on writing skills that lead to 3 aspects, organization, vocabulary, and grammar. In this study, the researcher used audio-visual media in the form of animal animation videos as a form of treatment. The researceher used report text in the form of animal explanations. This study focused on the use of audio-visual media at SMPN 2 Masjid Raya by using a random sampling technique. The researcher used a population from class 9 with a total of 5 classes and a sample of 2 classes as the experimental class and the control class. The number of students in both classes was 31 students. This study collects data using tests and interviews. The data is processed by descriptive statistics. The results show that the result of the t-test is 10.950 and with df = n-2 or df = 31-2 = 29, the t-table is 2.045. With test criteria tcount from ttable or 10.950 2.048 at a significance level of (a) 5%. This means, there is a significant effect on improving students' writing skills in using audio-visual media. The use of audio-visual media is recomemded for improving student’s writing skills.